Soil Phosphorus Dynamics under Long-Term No-Till with Offseason Intercropping Systems - Rigon, João Paulo Gonsiorkiewicz; Vilela, Rafael Gonçalves [UNESP]; Teles, Ana Paula Bettoni; Bernart, Leila [UNESP]; Pavinato, Paulo Sérgio; Calonego, Juliano Carlos [UNESP]; Crusciol, Carlos Alexandre Costa [UNESP] (Springer Nature, 2024)
Purpose A long-term no-till study was conducted to determine whether offseason intercropping systems with maize as the cash crop increase crop straw inputs and the yield of soybean as the main crop and alter soil P dynamics compared with monocropped offseason maize. Methods The experiment was conducted between 2019 and 2021 in a randomized complete block design with four replications and four cropping systems in the offseason (fall–winter): maize alone; maize + palisade grass (U. brizantha); maize + sunn hemp (C. spectabilis); and maize + palisade grass + sunn hemp. Leaf P content, crop straw, and soybean and maize yields were analyzed, and chemical P fractionation was performed at soil depths of 0–0.05, 0.05–0.1, and 0.1–0.2 m. Results The intercropping systems affected the labile and moderately labile P pools at a depth of 0–0.05 m. On average, the intercropping systems decreased soil inorganic P (Pi) extracted by anion exchange resin (PiAER) by 26% compared with monocropped maize. In addition, the intercropping systems increased moderately labile organic P (Po) while simultaneously reducing the Pi pool. Intercropping palisade grass and/or sunn hemp with maize increased the depletion of labile and moderately labile Pi pools due to higher plant P demand driven by plant biomass. On the other hand, higher root exudates and root detritus enhanced the accumulation of moderately labile organic P under highly weathered soils. Intercropping palisade grass enhanced the yield of the main crop, i.e., soybean, but limited maize yield, presumably by creating an insufficient N supply for maize.
Keywords: Crop rotation; Crop straw; P fractionation; Soil P lability